2015
DOI: 10.1038/nrm3958
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and selectivity in mRNA translation on the endoplasmic reticulum

Abstract: Pioneering electron microscopy studies defined two primary populations of ribosomes in eukaryotic cells: one freely dispersed through the cytoplasm and the other bound to the surface of the endoplasmic reticulum (ER). Subsequent investigations revealed a specialized function for each population, with secretory and integral membrane protein-encoding mRNAs translated on ER-bound ribosomes, and cytosolic protein synthesis was widely attributed to free ribosomes. Recent findings have challenged this view, and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
187
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(195 citation statements)
references
References 121 publications
7
187
0
1
Order By: Relevance
“…However, their data also showed many transcripts encoding non-ER trafficked proteins to also be engaged with ER-proximal ribosomes (Reid and Nicchitta 2015b). Similarly, several other studies have suggested a critical role of ER-proximal ribosomes in translating several cytoplasmic proteins (Reid and Nicchitta 2015a). Here, we found that 5IM transcripts-including those that are not ERtrafficked or mitochondrial-were significantly more likely to exhibit binding to ER-proximal ribosomes (Fig.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, their data also showed many transcripts encoding non-ER trafficked proteins to also be engaged with ER-proximal ribosomes (Reid and Nicchitta 2015b). Similarly, several other studies have suggested a critical role of ER-proximal ribosomes in translating several cytoplasmic proteins (Reid and Nicchitta 2015a). Here, we found that 5IM transcripts-including those that are not ERtrafficked or mitochondrial-were significantly more likely to exhibit binding to ER-proximal ribosomes (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…In addition to ribosomes directly resident on the ER, an interesting possibility is the presence of a pool of peri-ER ribosomes (Jan et al 2015;Reid and Nicchitta 2015a). Association of 5IM transcripts with such a peri-ER ribosome pool could potentially explain the observed correlation of 5IM status with binding to ER-proximal ribosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In what represents a pronounced departure from the current textbook thinking (1), they argue that "the ER is a primary site of general protein synthesis" (2) and that ribosomes stay stably associated with the endoplasmic reticulum (ER) through many rounds of translation. As they point out, if the ER were the primary site of translation of both secreted and cytosolic proteins, this would complicate the interpretation of our ribosome exchange experiments.…”
mentioning
confidence: 99%
“…One promising candidate is the enrichment of mRNA encoding organellar proteins in proximity to these organelles. Such mRNA enrichment has been described for fractions containing predominantly peroxisomes (Zipor et al, 2009), mitochondria (Kaltimbacher et al, 2006;Eliyahu et al, 2010), chloroplasts (Weis et al, 2013), or the ER (Reid and Nicchitta, 2015), but only the latter was independent of translation (Pyhtila et al, 2008;Jagannathan et al, 2014).…”
Section: Additional Levels Of Regulationmentioning
confidence: 99%